Etiological Agents of Health-care associated Surgical Site Infections - Rita Treimane; Aija ?ilevi?a; Uldis Viesturs (Bioautomation, 2007)
Surgical site infection is the second most common nosocomial (health-care associated) infection among hospitalized patients and is a significant public health problem worldwide. Infections caused by multiresistant microorganisms are of special concern because of difficulties to treat them. From 1484 clinical samples, we isolated 1117 cultures of different gram-positive and gram-negative microorganisms. The leading agents were S. aureus and coagulase-negative Staphylococci. Methicillin resistance among S. aureus was low, while it exceeded 50% in CoNS. From gram-negative bacteria, representatives of the family Enterobacteraceae and non-fermenting rods were isolated in similar amounts. ESBL producers among E. coli and K. pneumoniae were not registered.